Vascular adaptations induced by 6 weeks WBV resistance exercise training. (20th September 2012) - Weber, Tobias; Beijer, Åsa; Rosenberger, André; Mulder, Edwin; Yang, Pengfei; Schönau, Eckhard; Bloch, Wilhelm; Rittweger, Jörn
Summary Background The impact of whole‐body vibration (WBV) upon the cardiovascular system is receiving increasing attention. Despite numerous studies addressing the acute cardiovascular effects of WBV training, very little is known regarding long‐term adaptations in healthy humans. Methods A 6‐week training study, with a 70 days follow‐up was designed to compare resistive exercise with or without super‐imposed whole‐body vibrations. Arterial diameter, intima media thickness and flow‐mediated dilation (FMD) were assessed by ultrasonography in the superficial femoral artery (SFA), the brachial (BA) and the carotid arteries (CA). Results SFA resting diameter was increased from 6·22 mm (SD = 0·69 mm) at baseline to 6·52 mm (SD = 0·74 mm) at the end of the training period (P = 0·03) with no difference between groups (P = 0·48). Arterial wall thickness was significantly reduced by 4·3% (SD = 11%) in the CA only (P = 0·04). FMD was not affected by any of the interventions and in any of the investigated arteries. Conclusion To the best of our knowledge, this has been the first study to show that the superposition of vibration upon conventional resistance exercise does not have a specific effect upon long‐term vascular adaptation in asymptomatic humans. Our findings seem to be at variance with the findings observed in a bed‐rest setting. One possible explanation could be that the independently saturable effects of flow‐mediated versus acceleration‐related endothelial shear stresses on arterial structure and function differ between ambulatory and bed‐rest conditions.